The longest filled common subsequence problem - Castelli, Mauro (2017)
Castelli, M., Dondi, R., Mauri, G., & Zoppis, I. (2017). The longest filled common subsequence problem. In 28th Annual Symposium on Combinatorial Pattern Matching, CPM 2017 (Vol. 78). [14] Schloss Dagstuhl- Leibniz-Zentrum fur Informatik GmbH, Dagstuhl Publishing. https://doi.org/10.4230/LIPIcs.CPM.2017.14